2011
DOI: 10.1007/s00018-011-0691-9
|View full text |Cite
|
Sign up to set email alerts
|

Axonal commissures in the central nervous system: how to cross the midline?

Abstract: Organisms with bilateral symmetry elaborate patterns of neuronal projections connecting both sides of the central nervous system at all levels of the neuraxis. During development, these so-called commissural projections navigate across the midline to innervate their contralateral targets. Commissural axon pathfinding has been extensively studied over the past years and turns out to be a highly complex process, implicating modulation of axon responsiveness to the various guidance cues that instruct axon traject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 126 publications
1
46
0
Order By: Relevance
“…3h-i), suggesting that the endo-IWR-1 treatment might interfere with ventral midline formation. By analogy to the known roles of slit and netrin during axon guidance in the CNS of vertebrates and arthropods 32 , mild defects in ventral midline formation might explain the axon guidance defects that we observed in endo-IWR-1-treated embryos. Finally, we observed that Pdu-axin expression is strongly reduced in endo-IWR-1-treated embryos (Fig.…”
Section: Resultssupporting
confidence: 54%
“…3h-i), suggesting that the endo-IWR-1 treatment might interfere with ventral midline formation. By analogy to the known roles of slit and netrin during axon guidance in the CNS of vertebrates and arthropods 32 , mild defects in ventral midline formation might explain the axon guidance defects that we observed in endo-IWR-1-treated embryos. Finally, we observed that Pdu-axin expression is strongly reduced in endo-IWR-1-treated embryos (Fig.…”
Section: Resultssupporting
confidence: 54%
“…Expressed at the floor plate by glial cells, ephrin B3 acts with short-range activity, whereas Slit2/3 and Sema3B are secreted factors with potentially longer range activity. Combinations and sequences of ligand accessibility and guidance receptor availability are likely to play crucial roles in providing spatial and temporal coordination of guidance signals at the floor plate (Dickson and Zou, 2010;Kaplan et al, 2014;Nawabi and Castellani, 2011). In addition, the common use of Syk signaling would provide an efficient way to ensure the integration of the various guidance forces.…”
Section: Integration Of Guidance Signals By Itam-based Signalingmentioning
confidence: 99%
“…Although commissural neurons in the vertebrate and invertebrate central nervous system have provided us with a wealth of information on the molecular mechanism of axon guidance (Dickson and Gilestro, 2006;Evans and Bashaw, 2010;Nawabi and Castellani, 2011), knowledge of the intrinsic genetic programs employed is still limited. For instance, it has remained obscure whether the action of a single transcription factor can activate downstream molecular programs required for midline crossing, or whether the parallel actions of several transcription factors are needed for this task.…”
Section: Homeodomain Factor Selectively Expressed By Midbrain Commissmentioning
confidence: 99%